ALPHA–2–MACROGLOBULIN COMPLEXES WITH IGG ANTIBODIES, PLASMIN, AND THEIR INTERRELATION WITH OTHER FACTORS OF HUMORAL IMMUNITY DURING THE DEVELOPMENT OF RHEUMATOID ARTHRITIS - V. N. Zorina; N. A. Trofimenko; S. V. Arkhipova; R. M. Zorina; N. A. Zorin (Медицинская иммунология)
Abstract. Human alpha–2–macroglobulin (α2–MG) acts as a broad–spectrum cytokine and proteasebinding protein, and it represents an evolutionarily conserved arm of innate immune system. Meanwhile, previous studies have shown that rheumatoid arthritis (RA) development may cause alterations in α2–MG conformation and lessen its ability to bind and utilise regulatory substances. We investigated serum contents of α2–MG–IgG and α2–MG–plasmin complexes, as well as total concentrations ofα2–MG, plasmin (Pl), IgG, IL–6, IL–1β, TNFα and Rf–IgM, in order to evaluate the levels of anti–α2–MG antibody production in sera of patients with different degrees of RA activity and some interrelations of preformed immune complex with some other substances implicated in RA development. Serum samples were obtained in acute phase of RA, before the treatment was started. We have revealed significantly increased levels of α2–MG–IgG complex in the groups with severe RA, accompanied by increase in total IgG levels, without significant changes in total α2–MG concentrations. We have also demonstrated that increased levels of Pl–α2–MG complex did correspond to the severity of disease, and showed statistically high correlation with α2–MG–IgG levels. We have found a significant increase of IL–1β, IL–6, TNFα and Rf–IgM in RA, in absence of significant correlations with α2–MG–IgG contents. The results obtained allow us to suggest that abundant accumulation of serum antibodies to α2–MG or Pl–α2–MG complex during inflammation in the people with innate α2–MG deficiency, followed by increased levels of proinflammatory cytokines, may provoke a cascade–like development of RA. Serum levels of α2–MG may serve as prognostic marker in RA. (Med. Immunol., 2005, vol.7, № 5–6, pp. 557–562)